Preliminary Study of Buffer Ratio in Protein Extraction from Placental Cotyledons of Kedah-Kelantan Cattle - Y. Y. Tee; K. Mat; M. A. Adam; N. D. Rusli; C. H. Hasnita; H. N. Mohd Khalid (Tropical Animal Science Journal, 2020)
Protein extraction is a preliminary step of protein purification which mainly focus on maximization of total protein yield. The heterogeneous properties cause diversification of protein; therefore, there is no absolute protocol in protein extraction. The ratio of buffer gives different protein concentrations in different types of mammalian tissues, and this condition leads to the study of optimization of buffer ratio to obtain a better total protein yield. The objectives of this study were to compare the total protein yield based on three different ratios of buffer used. The phosphate buffer saline (PBS), radioimmunoprecipitation assay (RIPA) buffer, and RIPA buffer with the addition of protease inhibitor (Pi) were used with the ratios of 1:1, 1:3, and 1:5. Fetal cotyledons removed from the placenta have undergone mechanical disruption, incubation, sonication, and centrifugation. The supernatant was retained and quantified with Bradford assay to determine the total protein yield based on the standard curve of bovine serum albumin (BSA). There was a statistically significant different between buffer ratio (p<0.5) in RIPA and RIPA with addition of protease inhibitor buffers. RIPA buffer with the ration of 1:1 gave the best total protein yield (194.880±15.089 mg/g). As a conclusion, there was a significant interaction between buffer types and have greatly enhanced the total protein yield obtained from placental cotyledons of Kedah-Kelantan cattle.